Decision Making in Business: Using the Tools of the Philosophical Practice - Vasile Hațegan (Ovidius University Annals: Economic Sciences Series, 2020)
The decision making in business is an essential component of the management, where the leader, together with his team, are concerned with identifying and finding the optimal solutions to support the decision-making process or to meet the organization's objectives reflected in the company mission statement. The paper highlights the role that philosophical practice can play in organizations, which provides the management team with specific philosophical tools, such as short Socratic dialogue or dilemma training, as well as practical ways to apply critical thinking, as a tools including in the management process, thus increasing the decision-making capacity for the leaders of the organizations. The critical thinking, often considered to be specific to the educational system, finds its application in the business environment, with help of the philosophical consulting, a specialized practice of philosophical counseling.